2017
DOI: 10.5414/alx01401e
|View full text |Cite
|
Sign up to set email alerts
|

Food-induced anaphylaxis and cofactors – data from the anaphylaxis registry

Abstract: Food allergens are frequent causes of anaphylaxis. In particular in children and adolescents they are the most frequent elicitors of severe allergic reactions, and in adults food allergens rank third behind insect venom and drugs. Since July 2006 severe allergic reactions from Germany, Austria, and Switzerland are collected in the anaphylaxis registry. Currently 78 hospitals and private practises are connected. From July 2006 until February 2009 1,156 severe allergic reactions were registered. Among children a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 17 publications
1
17
0
5
Order By: Relevance
“…The concomitant allergic history of patients in this study was similar to that reported in previous studies, with atopic dermatitis being the most common in children, and allergic rhinitis being the most common in adults. 10 , 17 The proportion of children with asthma was relatively higher in the European registry than that in our region, possibly due to the variance in the age distribution of patients registered in each study and the difference in the prevalence of asthma. 18 Unlike other studies, we classified that a previously known food allergy is a separate medical history and identified that >50% of children in this registry had a previously known food allergy.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…The concomitant allergic history of patients in this study was similar to that reported in previous studies, with atopic dermatitis being the most common in children, and allergic rhinitis being the most common in adults. 10 , 17 The proportion of children with asthma was relatively higher in the European registry than that in our region, possibly due to the variance in the age distribution of patients registered in each study and the difference in the prevalence of asthma. 18 Unlike other studies, we classified that a previously known food allergy is a separate medical history and identified that >50% of children in this registry had a previously known food allergy.…”
Section: Discussionmentioning
confidence: 66%
“…Physical exercise was the most common cofactor of anaphylaxis in adults in this study, whereas drug intake or tiredness was a more common cofactor among adults in other studies. 29 , 30 To date, little is known about the cofactors affecting the induction and augmentation of severe allergic reactions. In future studies, cofactors related with anaphylaxis should be more thoroughly evaluated so that patients can be better informed about the risk factors amplifying severe allergic reactions.…”
Section: Discussionmentioning
confidence: 99%
“…The observed clinical response might differ between food allergic patients ranging from mild local symptoms like the oral allergy syndrome to severe systemic reactions such as anaphylaxis [1,2]. Actually, food allergy is among the main causes for potentially life-threatening anaphylaxis accounting for 41% of fatal reactions as reported to an European anaphylaxis registry [3]. For an efficient definition of allergy prevention measures, a profound mechanistic knowledge on sensitizing events is fundamental.…”
Section: Introductionmentioning
confidence: 99%
“…Cofactors reportedly play a role in approximately 30% of anaphylactic reactions in adults 7,8) versus 14-18.3% in children. 5,8,9) In one study, at least one cofactor was reported in 40% of children with anaphylactic reactions. 10) Most evidence on cofactors arose from studies in adult patients; thus, the role of cofactors has not yet been optimally studied in children.…”
Section: A C C E P T E D a R T I C L Ementioning
confidence: 99%
“…Epidemiological studies reported that infections are associated with 2.5-3% of anaphylactic reactions in children. 5,8,9) In the clinical setting, infection is a commonly suspected augmentation factor for anaphylaxis. A possible association between infection and anaphylactic reactions following allergen immunotherapy is often reported.…”
Section: Acute Infectionsmentioning
confidence: 99%